Factors Affecting Adoption of Recommended Cauliflower Production Technology in Nepal - Pankaj Raj Dhital; Narayan Raj Joshi (Turkish Journal of Agriculture: Food Science and Technology)
Binary logit regression model of econometrics was used to identify the factors affecting adoption of recommended agricultural technology by the commercial farmers of Nepal. A survey was carried out in 2012 in 120 households from Kavre district, Nepal. The objective was to appraise factors affecting adoption of recommended technology of cauliflower, finding out the level of adoption, identifying the constraints of cauliflower cultivation, assessing the perceived level of satisfaction and studying the relationship of certain selected variables on the adoption. Education, Occupation, contact with Personal Localite sources of information, Group membership and Experience were the most influencing factors for adoption of recommended technology. Though, other factors were not strong enough to contribute significantly but indirectly influence the adoption decision of farmers as combined effects. Occupation was found as negatively associated. Landholding size was strongly and positively influencing among the non significant factors. The level of satisfaction and the constraints of cauliflower production were also identified. Transfer of technology will be effective if and only if the client adopts the technology. For an effective transfer of technology, it is better to go for activities for the welfare of the socioeconomic factors of the farmers.